Hepatocystic fistula treated by cysticjejunal diversion - Palma, Eduardo; Fernández, Eliexer; Danza, Rómulo (Cirugía del Uruguay, 2020)
1) Areport is carried out of a case of suppurative calcified giant hepatic-hidatid cyst, with marked aero -anaerobian infection and very poor- general condition, treated by plain evacuation, extenal drainge and antibiogicogerapy, without drainage of the main biliary duct and with excellent course. 2) The chronic external hepatic --cystic fistula was treated by means of a Y shaped jejunal cystic anastomosis at the 4th jejunal loop, with gratifying results.